Financial performance analysis of sharia banking with maqashid shariah index method - Saiful Muchlis; Munir Munir; Rimi Gusliana Mais (LPMP Imperium, 2022)
This study aims to determine the financial performance of Islamic banking using the Maqashid Shariah Index financial approach. This study uses a type of descriptive research with a quantitative approach. The population of this study is Islamic commercial banks in Indonesia operating from 2015 to 2020. The sample was determined based on the purposive sampling method, with a total sample of 10 Islamic commercial banks with six years of observation. Data was used in this study in the form of secondary data. The data collection technique uses the documentation method in the form of annual financial reports (annual reports) on the official website of each Islamic commercial bank. The results of the study prove that 1) Bank Muamalat Indonesia (BMI) ranks first in calculating the performance of the maqashid sharia index, and Bank BTPN Syariah (BTPNS) ranks lowest. 2) In general, Islamic banks in Indonesia have fulfilled the three objectives of sharia well, so in the future, this good achievement needs to be developed and improved. Management may be made to determine and implement a reasonable and also appropriate strategy, such as increasing the knowledge and capabilities of the company's human resources, optimizing capital, developing various financing products, and maintaining a spirit of cooperation between Islamic financial institutions with related customers